A new neurosurgical adjustable pressure suction apparatus with a mechanically controlled air inlet: the study of precise regulation and atraumatic suction - Nie, Pan; Chen, Mengxi; Zhang, Jibo; Pan, Meicheng; Gu, Xiqian; Xu, Chengshi; Li, Zhengwei; Zhang, Jianjian; Zhao, Wenyuan; Li, Xiang; Zhang, Jie; Chen, Jincao (Frontiers in Neurology, 2022)
Background An essential surgical tool in neurosurgery is the suction tube. The skillful and accurate use of a suction tube facilitates the neurosurgical operation. Objective This study is to verify the practicality of an adjustable pressure suction tube (APS tube) and to explore the ideal APS tube diameter and tip negative pressure for different intracranial structures. Methods APS tubes were used to aspirate brain tissues and carotid arteries of rats. Laser speckle contrast imaging (LSCI) was used to record the blood flow velocity (BFV). We measured APS tube diameter, air inlet size, tip negative pressure and central negative pressure and calculated the correlation between them. In our department, intraoperative real-time parameters including APS tube diameter, length, air inlet size, and central negative pressure were recorded, and the tube tip negative pressure suitable for different intracranial structures and parts was calculated. Results All experiments were carried out using APS tubes. Experiments on rats objectively reflected a severe structural damage to the brain and blood vessels by the suction tube, which might even result in an irreversible reduction in blood flow., Rat carotid arteries and brain tissue suffered severe damage when the tip negative pressure exceeded 33.4 ± 1.8 and 29.2 ± 2.0 kPa, respectively. BFV failed to return to the preoperative level 3 min after the operation (p < 0.05), and this decrease was more pronounced when the suction tube diameter was large (p < 0.05). The tip negative pressure was positively and negatively correlated with central negative pressure and the air inlet size, and was independent of APS tube diameter. A total of 50 operations including 39 tumor resection operations and 11 moyamoya disease bypass operations were recorded. Large-diameter APS tubes (3.5 mm) with an closed air inlet were frequently used to maintain a greater tip negative pressure before the incision of dura mater. When important structures such as motor cortex and brainstem were involved, 1.5- or 2.0-mm-diameter APS tubes were mostly used, and an air inlet was opened up to 0.7–2.1 mm to maintain a safe tip negative pressure (7.4–27.9 kPa). Conclusion APS tubes with a mechanical knob provide stable and precise adjustment of the tip negative pressure, avoiding excessive negative pressure that causes serious damage to the intracranial structure. And, this allows the surgeon to hold the suction tube more freely and operate at any angle with an appropriate fulcrum near the incision to achieve efficient atraumatic suction and enhance surgical safety.